Pendidikan Akhlak Pendakwah dalam Surat Maryam Ayat 41-50 Menurut Tafsir Fathul Qadir - Muhammad Utama Al Faruqi (Islamic University of Indonesia, 2020)
Da'wah is one of the pillars of upholding the noble religion of Islam. As a form of worship for the perpetrators, and a way of calling out the truth to people outside of Islam, or who are in Islam. So, it is very necessary to have serious attention in instilling the characteristics of the da'wah implementers, or the preachers. Especially in their morality, as one of the most important assets in the success of the da'wah. Given that in the present era, there are so many people who dedicate themselves to da'wah, but in reality, they are the ones who destroy the image of Islam and the preaching itself with their bad behavior and morals. In the Al Quran, in Surah Maryam verses 41 to 50, the dialogue of the Prophet Abraham - 'alayhis salam - is narrated as one of the most important role models for preachers across generations. The preacher must have intellectual and emotional intelligence, must be patient and elegant. Without criticizing and making people run away from the religion. In fact, the characteristics of Muslims in Indonesia are the characteristics of being gentle, friendly, and cooperative. These findings contribute to the preachers so that what they preach brings many benefits, not harm.